Perfusion-sensitive MR Imaging of Gliomas: Comparison between Gradient-echo and Spin-echo Echo-planar Imaging Techniques - Sugahara, Takeshi; Korogi, Yukunori; Kochi, Masato; Ushio, Yukitaka; Takahashi, Mutsumasa (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: The different sensitivities to vessel size of gradient-echo echo-planar imaging (GE-EPI) and spin-echo EPI (SE-EPI) might indicate the relative cerebral blood volumes (rCBVs) of different tumor sizes. The techniques of GE-EPI and SE-EPI were compared for detecting low- versus high-grade gliomas.METHODS: Six patients with low-grade gliomas and 19 patients with high-grade gliomas underwent two perfusion-sensitive MR procedures, one produced by a GE- and the other by an SE-EPI technique. Maximum rCBV ratios normalized with rCBV of contralateral white matter were calculated for evaluation. P < .05 was considered statistically significant.RESULTS: Maximum rCBV ratios of high-grade gliomas obtained with the GE-EPI technique (mean, 5.0 ± 2.9) were significantly higher than those obtained with the SE-EPI technique (mean, 2.9 ± 2.3) (P = .02). Maximum rCBV ratios of low-grade gliomas obtained with the GE-EPI technique (mean, 1.2 ± 0.7) were almost equal to those obtained with the SE-EPI technique (mean, 1.2 ± 0.6), and there was no significant difference (P = .66). The difference in the maximum rCBV ratios between the low- and high-grade gliomas reached significance when obtained with the GE-EPI technique (P = .01).CONCLUSION: The GE-EPI technique seems more useful for detecting low- versus high-grade gliomas than the SE-EPI technique.